Integrating Interprofessional Education and Cultural Competency Training to Address Health Disparities. Issue 2 (3rd April 2018) - McElfish, Pearl Anna; Moore, Ramey; Buron, Bill; Hudson, Jonell; Long, Christopher R.; Purvis, Rachel S.; Schulz, Thomas K.; Rowland, Brett; Warmack, T. Scott
ABSTRACT: Problem : Many U.S. medical schools have accreditation requirements for interprofessional education and training in cultural competency, yet few programs have developed programs to meet both of these requirements simultaneously. Furthermore, most training programs to address these requirements are broad in nature and do not focus on addressing health disparities. The lack of integration may reduce the students' ability to apply the knowledge learned. Innovative programs that combine these two learning objectives and focus on disenfranchised communities are needed to train the next generation of health professionals. Intervention : A unique interprofessional education program was developed at the University of Arkansas for Medical Sciences Northwest. The program includes experiential learning, cultural exposure, and competence-building activities for interprofessional teams of medicine, nursing, and pharmacy students. The activities include (a) educational seminars, (b) clinical experiential learning in a student-led clinic, and (c) community-based service-learning through health assessments and survey research events. Context : The program focuses on interprofessional collaboration to address the health disparities experienced by the Marshallese community in northwest Arkansas. The Marshallese are Pacific Islanders who suffer from significant health disparities related to chronic and infectious diseases. Outcome : Comparison tests revealed statistically significant changes in participants' retrospectively reported pre/posttest scores for Subscales 1 and 2 of the Readiness for Interpersonal Learning Scale and for the Caffrey Cultural Competence in Healthcare Scale. However, no significant change was found for Subscale 3 of the Readiness for Interpersonal Learning Scale. Qualitative findings demonstrated a change in students' knowledge, attitudes, and behavior toward working with other professions and the underserved population. Lessons Learned : The program had to be flexible enough to meet the educational requirements and class schedules of the different health professions' education programs. The target community spoke limited English, so providing interpretation services using bilingual Marshallese community health workers was integral to the program's success.